Wild Edible Plants Used by Endangered & Indigenous Raji Tribe in Western Nepal - Thapa, Lal B; Dhakal, Til Maya; Chaudhary, Raghunath (International Journal of Applied Sciences and Biotechnology, 2014)
The Rajis are one of the endangered indigenous people distributed in western part of Nepal enriched in their own mother tongue, culture, beliefs and practices. Owing to lack of proper documentation, the traditional knowledge of uses and practices on wild edible plants by such an endangered community is about to extinct. This paper aims to present the traditional practices and use of wild edible plants by Raji people in Nepal. Our study found that a total of 67 wild edible plant species included in 56 genera and 38 families used by Raji people. Out of them 62 species were angiosperms, one species was Gymnosperm and 4 species were Pteridophytes. The results of study show that Rajis have their traditional way to use different parts of wild plants such as seeds, fruits, leaves, shoots, roots and tubers in the forms of vegetables, pickles, juice, and raw or as fruits. DOI: http://dx.doi.org/10.3126/ijasbt.v2i3.10969 Int J Appl Sci Biotechnol, Vol. 2(3): 243-252